Analisis Model Tarikan Perjalanan pada Kawasan Perdagangan Kota Purbalingga (Studi Kasus: Pasar Bobotsari Purbalingga) (Indonesian Journal of Civil Engineering Study, 2026)
Trip generatioan is a concept in transportation planning that explains the relationship between economic activity in an area and the traffic movements it generates. This concept is essential for understanding how market activities influence community mobility and transportation infrastructure needs. Travel, in this context, is defined as the movement of individuals from an origin to a destination to conduct various activities. This study aims to analyze the characteristics of people’s travel behavior to shopping areas and identify the factors that influence travel attraction to those areas. Data were collected through questionnaires distributed at Bobotsari Market in Purbalingga, involving a population of 11,125 people and a sample of 320 respondents. The analysis employed linear regression and correlation coefficient analysis using SPSS software. Based on the results, the model of travel attraction to the Bobotsari Market shopping area is represented by the equation: Y = 1.408 – 0.207(X3) +  0.231(X4) – 0.028(X10), where X3 refers to building floor area, X4 to parking area, and X10 to the price of goods. The characteristics of travelers show that most respondents have 3–4 family members and predominantly use private motorcycles. Motorcycle use is strongly associated with limited parking space, crowded market conditions, travel distances of 2–4.9 km, travel times of 6–10 minutes, and low transportation costs. Most travelers are women aged 21–40 years, originating from the Bobotsari area. The regression results indicate that the building floor area (X3) with sig. 0.023 < 0.05, parking area (X4) with sig. 0.009 < 0.05, and price of goods (X10) with sig. 0.013 < 0.05 significantly influence travel attraction (Y). These findings confirm that larger building space, adequate parking, and affordable goods play key roles in attracting visitors. Several recommendations can be proposed to manage trip attraction to the market, including integrating transportation and land-use planning, improving parking layout to reduce congestion, enhancing pedestrian access, and strengthening public transportation connectivity to the market area.